SUICÍDIO, O JOVEM E A ESCOLA: ANÁLISE DO RETRATADO NA MÍDIA JORNALÍSTICA E AS POSSÍVEIS ESTRATÉGIAS PARA ATUAÇÃO DO(A) PSICÓLOGO(A) NA ESCOLA - TIAGO SALSA CORREA (2021)
The phenomenon of suicide is currently growing all over the world including Brazil, and particularly the state where this research takes place, Mato Grosso do Sul, which has one of the highest suicide rates in the country. Before, its highest incidence was in adults and the elderly, although there has been a change in the last decade and the age group with the highest rate is now young. The public school appears in this light as one of the environments of social conflicts, where this target audience is at this particular stage of life. Thus, this research aims to verify what is portrayed in the regional journalistic media about school, youth and suicide and how this issue is posed in scientific productions that address the theme. This study is based on Historical-Dialectical Materialism, a foundation that forms the basis of Vigotski's Historical-Cultural Psychology and his interlocutors. In this search for an understanding of suicide, considering an analysis of the man who exterminates himself in his singular and universal characteristic. The path followed, the methodology, was carried out with bibliographic survey, and the verification of sources from the regional press. The analysis of suicide is mostly perceived in scientific works from a medical point of view, and through Historical-Cultural Psychology a look is sought from the psychic and social point of view, of the human and material relations that permeate our society. Keywords: Suicide. Historical-Cultural Psychology. Public school. School Psychology. Young.